The association between BNP, 6MWD test, DLCO% and pulmonary hypertension in sarcoidosis - Mirsaeidi, Mehdi; Omar, Hesham R.; Baughman, Robert; Machado, Roberto; Sweiss, Nadera (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Introduction: Pulmonary hypertension (PH) is a feared complication in patients with sarcoidosis.It is an important negative prognostic factor which is reflected as a priority given to these subjects for orthotopic lung transplantation. We evaluated the relationship between BNP, 6MWD test, DLCO% values and the severity of sarcoidosis-associated pulmonary hypertension. Methods: A retrospective chart review was conducted between January 2010 and January 2015 on consecutive confirmed adult subjects diagnosed with sarcoidosis. Demographics, medical comorbidities, clinical features, pulmonary function tests (PFTs), 6MWD test, transthoracic echocardiography, laboratory investigations, radiographic findings, treatment and outcome data were collected from medical records. Subjects with suspicion for PH (i.e. those with PASP ≥ 25 mmHg) were included in the study. PH severity was classified using PASP into mild (PASP 25-49 mmHg), moderate (50-69 mmHg) and severe (≥70 mmHg). We evaluated the strength of correlation between BNP, 6MWD test, DLCO% and the severity of PH. The association between variables was performed using Pearson correlation coefficient and results were considered statistically significant if P value was